THE IMPACT OF DIVERSIFICATION AND OWNERSHIP STRUCTURE ON EFFICIENCY: EVIDENCE FROM INDONESIA - Anggraeni; Basuki; Rahmat Setiawan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study aims to examine the effect of asset diversification and income diversification on bank efficiency in Indonesia. In addition, it also examines the effect of the interaction between ownership structure and independent commissioners on diversification on efficiency. The study used a sample of seventy-eight banks in Indonesia from 2010 - 2018. By using the Stochastic Frontier Analysis, the average bank efficiency is around 86 percent. The paper applies panel data methodology. The results show that: From model 1, finding a strong evidence that asset diversification and income diversification are positive and significant to the efficiency. Control variables are also significant and as expected. From model 2 shows that asset diversification is positive and significant, income diversification is positive but not significant. The government ownership structure strengthens the relationship between asset diversification and efficiency, but not income diversification. Meanwhile, independent commissioners strengthen the relationship between asset diversification and income diversification on efficiency. However, the results were not significant in terms of both ownership structure and independent commissioners in moderating the relationship between asset diversification and income diversification on bank efficiency. For control variable, size is positive and significant and for the risk bank, the result is negative and significant. JEL Classification D61, G21, G24, G33, L25 JEL Classification D61, G21, G24, G33, L25